0842 Myelin-oligodendrocyte glycoprotein antibody as a cause of acute disseminated encephalomyelitis with a neuromyelitis optica-like phenotype in adults. Issue 3 (9th February 2012) - Kitley, J; Woodhall, M; Waters, P; Leite, M I; Devenney, E; Craig, J; Vincent, A; Palace, J
Abstract : Neuromyelitis optica (NMO) is an autoimmune CNS disorder causing optic neuritis (ON) and longitudinally extensive transverse myelitis (LETM). Limited forms of the disease are called NMO spectrum disorder (NMOSD). Disease specific autoantibodies targeting aquaporin 4 (AQP4) can be found in the sera of most patients with NMO and in some with NMOSD. It is unclear whether AQP4 seronegative patients represent a distinct clinical subgroup of NMO/NMOSD or have a different condition. We describe four patients in whom we identified serum antibodies to myelin-oligodendrocyte glycoprotein (MOG) using a cell-based assay (cDNA courtesy of Dr K O'Connor, Yale, USA). All patients had AQP4-seronegative monophasic NMOSD with severe ON and/or LETM which recovered fully with steroids ± plasma exchange. Two patients relapsed during the acute phase when corticosteroids were withdrawn too quickly but none have experienced further relapses over mean follow-up of 12 months. Imaging abnormalities resolved fully following clinical recovery and MOG antibody titres decreased in all patients. MOG is an accessible myelin antigen that induces ADEM-like and NMO-like experimental autoimmune encephalomyelitis in rodents. MOG antibodies have been recently described in paediatric ADEM (O'Connor et al 2007; Lalive et al 2010). Our cases suggest that MOG antibodies may be a biomarker for ADEM with an NMO-like phenotype in adults. These patients appear to have a good clinical outcome. We recommend that MOG antibodies should be measured in AQP4 negative NMOSD patients.